2021
DOI: 10.1002/jpen.2203
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition competencies for undergraduate medical education: Results of an international interdisciplinary consensus

Abstract: Background The gap between the nutrition education provided to medical students and the nutrition competencies and attitudes needed for physicians to provide adequate nutrition care is a global concern. There is no universally accepted benchmark on nutrition competencies for doctors. The objective of this study was to establish, by expert consensus, the objectives of undergraduate nutrition medial education, the nutrition core competencies, and strategies for curriculum development in medical nutrition educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
1
3
0
5
Order By: Relevance
“…Slightly above half said there was insufficient nutrition training for doctors in Nigeria. This was similar to the findings of Cardenas et al (21) on Nutrition in medical education in Latin America, where the medical students also had positive attitudes toward nutrition but insufficient nutrition training for doctors. Almost half of the respondents reported that physicians have little impact on the patient's ability to lose weight, for patients who needed weight loss and some of the students could not recall the formula for calculating BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Slightly above half said there was insufficient nutrition training for doctors in Nigeria. This was similar to the findings of Cardenas et al (21) on Nutrition in medical education in Latin America, where the medical students also had positive attitudes toward nutrition but insufficient nutrition training for doctors. Almost half of the respondents reported that physicians have little impact on the patient's ability to lose weight, for patients who needed weight loss and some of the students could not recall the formula for calculating BMI.…”
Section: Discussionsupporting
confidence: 89%
“…Firstly, we call upon Medical Deans’ Associations to make nutrition education compulsory in medical training so as to equip medical professionals to adequately respond to the global burden of NCDs. We recommend that medical curricula in Australia and globally adopt a Nutrition Competency Framework spanning the prevention and treatment of diseases relating to nutrition, in line with benchmarks developed by recent international interdisciplinary consensus [ 23 ]. Finally, we call upon researchers and universities to develop, pilot and assess innovative nutrition initiatives in medical curriculums, such as ‘culinary medicine’ programs.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio reciente a nivel de América Latina, se realizó una encuesta en 17 países que incluyó 22 directores de facultades de medicina, más o menos una universidad por país, el cual concluyó. Este mostró que se dedicaban 47 horas al estudio de la nutrición (38). Para tener un contexto, según la Asociación Colombiana de Facultades de Medicina (ASCOFAME), durante 2016 en Colombia, existían 58 facultades de medicina (39), por esta razón, el número de horas reportado en el estudio de América Latina puede ser mucho menor, debido a que es posible, que quienes contestaron la encuesta, podrían tener un interés particular en nutrición.…”
Section: Discussionunclassified